DETERMINATION OF MACHINING PARAMETERS OF COLD ROLL-BEATING SPLINE SURFACE ROUGHNESS - LIU DongYa; WANG XiaoQiang; LIU Fei; CUI FengKui; ZHU QiPing; LIU ZhiFei (Jixie qiangdu)
In order to obtain the cold roll-beating spline surface roughness processing parameter domain suitable for different working conditions. Based on the principle of cold roll-beating spline forming,carry out cold roll-beating spline surface roughness test,using the test results to construct a surface prediction model for surface roughness response of cold roll-beating spline,using the analysis of variance,test sample test and comparison of experimental and predicted values,it is verified that the predictive model is feasible. Analyze the variation of the rotational speed of the rolling wheel,the feed rate of the workpiece and the surface roughness,the processing parameter domain of the surface roughness of the cold roll-beating spline is determined based on the surface roughness accuracy level comparison table. The results show: The rotational speed of the rolling wheel is 976 r/min ～ 2936 r/min,and the workpiece feed rate is in the range of 7 mm/min ～ 56 mm/min,with the gradual increase of the rotational speed of the rolling wheel and the feed rate of the workpiece,the surface roughness shows a trend of decreasing first and then increasing. Five sets of processing parameters were randomly extracted from the processing parameter fields corresponding to each accuracy level,and the maximum relative error between the surface roughness test value and the predicted value was 2. 75 %.Therefore,it is shown that the determined cold roll-beating spline surface roughness processing parameter domain is accurate and reliable. The research results have important application value and certain theoretical guiding significance for controlling the surface roughness of cold roll-beating spline.